Abuse and Neglect in Nursing Homes: The Role of Serious Mental Illness. (11th January 2022) - Jester, Dylan J; Molinari, Victor; Bowblis, John R; Dobbs, Debra; Zgibor, Janice C; Andel, Ross
Abstract: Background and Objectives: Nursing homes (NHs) are serving a large number of residents with serious mental illness (SMI). We analyze the highest ("High SMI") quartile of NHs based on the proportion of residents with SMI and compare NHs on health deficiencies and the incidence of deficiencies given for resident abuse, neglect, and involuntary seclusion. Research Design and Methods: We used national Certification and Survey Provider Enhanced Reports data for all freestanding certified NHs in the continental United States from 2014 to 2017 (14, 698 NHs; 41, 717 recertification inspections; 246, 528 deficiencies). Differences in the number of deficiencies, a weighted deficiency score, the deficiency grade, and the facility characteristics associated with deficiencies for abuse, neglect, and involuntary seclusion were examined in High SMI. Incidence rate ratios (IRRs) and odds ratios (ORs) were reported with 95% confidence intervals. Results: High-SMI NHs did not receive more deficiencies or a greater weighted deficiency score per recertification inspection. Deficiencies given to High-SMI NHs were associated with a wider scope, especially Pattern (IRR: 1.03 [1.00, 1.07]) and Widespread (IRR: 1.07 [1.02, 1.11]). High-SMI NHs were more likely to be cited for resident abuse and neglect (OR: 1.49 [1.23, 1.81]) and the policies to prohibit and monitor for abuse and neglect (OR: 1.18 [1.08, 1.30]) in comparison to all other NHs. Discussion and Implications: Although resident abuse, neglect, and involuntary seclusion are rarely cited, these deficiencies are disproportionately found in High-SMI NHs. Further work is needed to disentangle the antecedents to potential resident abuse and neglect in those with mental health care needs.